High-shear reinforced lignin-based magnetic adsorbent and preparation method and application thereof

CN122999149APending Publication Date: 2026-10-30SHIHEZI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611403922.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种高剪切强化木质素基磁性吸附剂及其制备方法和应用,用以解决现有的木质素基磁性吸附剂制备方法存在混合效率低、颗粒团聚严重、结构不可控的技术问题

Benefits of technology

本发明公开了一种高剪切强化木质素基磁性吸附剂的制备方法,该方法在纳米Fe3O4磁性颗粒制备、SiO2核壳包覆以及木质素有机组装的全过程中均引入高剪切反应器进行强化处理,在共沉淀阶段,高剪切产生的强烈剪切力、湍流和微观混合效应能够有效消除传统机械搅拌难以避免的局部浓度梯度与温度梯度,使沉淀剂与铁盐溶液在分子尺度上快速均匀混合,促进晶核同步形成并抑制其异常长大,从而获得粒径细小、分布窄且分散性优良的Fe3O4磁核,为后续复合吸附剂提供了高质量的磁性核心基础;在SiO2包覆和木质素组装阶段,持续的高剪切环境一方面强化了TEOS水解缩合过程中的传质效率,确保SiO2在磁核表面形成连续、完整且厚度均匀的保护壳层,另一方面改善了碱性木质素与APTES偶联后的接枝反应动力学,使木质素分子在无机壳层上实现定向、有序的组装,有效避免了因自聚集导致的活性位点屏蔽与结构塌缩,最终形成界面结合紧密、四级结构完整的磁性吸附剂。该方法从根本上解决了传统方法因混合不均、传质受限所导致的颗粒团聚严重和结构不可控的固有缺陷,从而使最终产物具备结构完整性和充分的活性位点暴露条件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999149A_ABST
    Figure CN122999149A_ABST
Patent Text Reader

Abstract

The application discloses a high-shear reinforced lignin-based magnetic adsorbent and a preparation method and application thereof, and belongs to the technical field of adsorbent materials.The method is introduced into a high-shear reactor for reinforced treatment in the whole process of nano Fe3O4 magnetic particle preparation, SiO2 core-shell coating and lignin organic assembly, active site shielding and structure collapse caused by self-aggregation are effectively avoided, and finally the magnetic adsorbent with close interface combination and complete quaternary structure is formed.The method fundamentally solves inherent defects of serious particle agglomeration and uncontrollable structure caused by uneven mixing and limited mass transfer in the traditional method, so that the final product has structural integrity and sufficient active site exposure conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of adsorbent materials technology, specifically relating to a high-shear-strength lignin-based magnetic adsorbent, its preparation method, and its application. Background Technology

[0002] With the rapid development of industries such as printing and dyeing, papermaking, metallurgy, electroplating, and fine chemicals, the discharge of industrial wastewater continues to increase. Among them, dye wastewater and heavy metal wastewater have become key challenges in the field of water pollution control due to their complex composition, high color intensity, strong toxicity, and poor biodegradability. Congo red, as a typical anionic azo dye, has the characteristics of strong water solubility, structural stability, and recalcitrant degradation, and is often used as a model pollutant to evaluate the decolorization performance of adsorption materials.

[0003] Adsorption is considered one of the most promising water pollution control technologies due to its simple operation, high treatment efficiency, and wide applicability. However, traditional adsorbents such as activated carbon and zeolite suffer from problems such as high preparation costs, difficult regeneration, insufficient selectivity, and inconvenient solid-liquid separation.

[0004] Lignin is the second most abundant aromatic polymer in nature after cellulose, with an annual biosynthesis of up to 50 billion tons, mainly derived from industrial waste such as papermaking black liquor and biorefining byproducts. Its molecular backbone is composed of phenylpropane units, and its side chains are rich in active functional groups such as phenolic hydroxyl groups, alcoholic hydroxyl groups, methoxy groups, and carboxyl groups. It can efficiently capture anionic dyes and heavy metal ions through multiple mechanisms, including electrostatic interactions, hydrogen bonding, and π-π stacking. However, raw lignin has inherent defects such as dense structure, low specific surface area, poor hydrophilicity, and easy aggregation, resulting in typically low adsorption capacity when used directly as an adsorbent. Introducing magnetic components such as Fe3O4 into lignin-based adsorbent materials can endow the materials with excellent magnetic response properties, enabling rapid solid-liquid separation.

[0005] Currently, the preparation of lignin-based magnetic adsorbents mainly adopts the conventional mechanical stirring co-precipitation method, which has defects such as low mixing efficiency, large mass transfer resistance, and uneven reaction, resulting in problems such as wide Fe3O4 particle size distribution, uneven lignin coating, and insufficient exposure of active sites. Summary of the Invention

[0006] The purpose of this invention is to provide a high-shear-strength lignin-based magnetic adsorbent, its preparation method, and its application, in order to solve the technical problems of low mixing efficiency, severe particle agglomeration, and uncontrollable structure in existing lignin-based magnetic adsorbent preparation methods.

[0007] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing a high-shear-strength lignin-based magnetic adsorbent, comprising the following steps: S1: Dissolve ferrous salts and ferric salts in water to obtain a mixed ferric salt solution; S2: The mixed iron salt solution was placed in a toothed high-shear reactor. Under stirring conditions, the precipitant was added to the mixed iron salt solution to carry out a high-shear co-precipitation reaction. After the reaction was completed, the solution was separated, washed, and dried to obtain nano Fe3O4 magnetic particles. S3: The obtained nano-Fe3O4 magnetic particles were dispersed in anhydrous ethanol, and tetraethyl orthosilicate was added. The reaction was carried out in a high-shear reactor. After the reaction was completed, the particles were separated, washed and dried in sequence to obtain Fe3O4@SiO2 core-shell particles. S4: Fe3O4@SiO2 core-shell particles were dispersed in anhydrous ethanol, and alkaline lignin solution and 3-aminopropyltriethoxysilane were added. The reaction was carried out in a high-shear reactor. After the reaction was completed, the particles were separated, washed and dried in sequence to obtain a high-shear reinforced lignin-based magnetic adsorbent.

[0008] Further, in S1, the divalent ferric salt is FeCl2·4H2O; the trivalent ferric salt is FeCl3·6H2O; and the Fe in the mixed ferric salt solution... 2+ with Fe 3+ The molar ratio is 1:1.5 to 1:2.5; The concentration of the mixed iron salt solution is 0.05~0.15 mol / L.

[0009] Further, in S2, the precipitant is ammonia water, and the mass concentration of the ammonia water is 25%~28%; the volume ratio of the ammonia water to the mixed iron salt solution is 1:10~1:30; and the ammonia water is added at a rate of 1~4 mL / min.

[0010] Furthermore, in S2, during the high-shear coprecipitation reaction, the high-shear reactor operates at a rotation speed of 3000~9000 rpm, a reaction temperature of 70~90℃, and a reaction time of 10~40 min.

[0011] Further, in S3, the mass ratio of the nano Fe3O4 magnetic particles to tetraethyl orthosilicate is 1:0.5~1:2; the volume ratio of the nano Fe3O4 magnetic particles to anhydrous ethanol is 1g:600mL. The addition of tetraethyl orthosilicate was carried out in a high-shear reactor at a rotation speed of 6000 rpm, a reaction temperature of room temperature, and a reaction time of 1 hour.

[0012] Furthermore, in S4, the alkaline lignin solution is obtained by mixing alkaline lignin and ammonia. The mass ratio of Fe3O4@SiO2 core-shell particles, alkaline lignin, and 3-aminopropyltriethoxysilane is 1:(1.5~2.5):(100~180); the molar ratio of Fe3O4@SiO2 core-shell particles to anhydrous ethanol is 0.05 g:300 mL. The reaction was carried out at 6000 rpm for 1 h at room temperature.

[0013] Furthermore, in step S4, after adding the alkaline lignin solution and 3-aminopropyltriethoxysilane, formaldehyde solution is also added, with the formaldehyde solution being fed at a rate of 3 mL / min; the amount of formaldehyde solution used is 15 mL.

[0014] Furthermore, the rotor linear velocity of the high-shear reactor is 5~50 m / s.

[0015] This invention also discloses a high-shear-strength lignin-based magnetic adsorbent, prepared by the above-described method; the adsorbent has a four-level core-shell structure, including an Fe3O4 magnetic core layer, a SiO2 stable shell layer, an APTES coupling layer, and a lignin adsorption layer; the SiO2 stable shell layer coats the outer surface of the Fe3O4 magnetic core, the APTES coupling layer is covalently grafted onto the outer surface of the SiO2 stable shell layer, and the lignin adsorption layer is chemically bonded to the APTES coupling layer.

[0016] This invention also discloses the application of the above-mentioned high-shear-strength lignin-based magnetic adsorbent in the adsorption of Congo red.

[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing a high-shear-enhanced lignin-based magnetic adsorbent. This method incorporates a high-shear reactor for enhanced treatment throughout the entire process of preparing nano-Fe3O4 magnetic particles, SiO2 core-shell coating, and lignin organic assembly. During the co-precipitation stage, the strong shear force, turbulence, and micro-mixing effect generated by high shear effectively eliminate local concentration and temperature gradients that are difficult to avoid with traditional mechanical stirring. This allows the precipitant and iron salt solution to mix rapidly and uniformly at the molecular scale, promoting the synchronous formation of crystal nuclei and inhibiting their abnormal growth, thereby obtaining Fe3O4 with fine particle size, narrow distribution, and excellent dispersibility. The four magnetic cores provide a high-quality magnetic core foundation for subsequent composite adsorbents. During the SiO2 coating and lignin assembly stages, the continuous high-shear environment enhances the mass transfer efficiency during TEOS hydrolysis and condensation, ensuring the formation of a continuous, complete, and uniformly thick protective shell of SiO2 on the magnetic core surface. Furthermore, it improves the grafting reaction kinetics after the coupling of alkaline lignin and APTES, enabling lignin molecules to achieve directional and orderly assembly on the inorganic shell. This effectively avoids active site shielding and structural collapse caused by self-aggregation, ultimately forming a magnetic adsorbent with tight interfacial bonding and a complete quaternary structure. This method fundamentally solves the inherent defects of traditional methods, such as severe particle agglomeration and uncontrollable structure due to uneven mixing and limited mass transfer, thus ensuring that the final product possesses structural integrity and sufficient exposure of active sites.

[0018] Furthermore, the method of this invention employs a high-shear reactor to enhance the co-precipitation process. Through intense shearing, turbulence, and micromixing, it significantly suppresses the heterogeneous growth and agglomeration of crystal nuclei caused by local pH gradients in traditional co-precipitation methods. XRD combined with Debye... Using the Scherrer equation, the characteristic diffraction peak (311) of Fe3O4 was selected to calculate the grain size of the product prepared at shear speeds of 3000 r / min, 6000 r / min, and 9000 r / min. As the shear speed increased, the half-width at half-maximum (FWHM) of the diffraction peak increased, and the grain size gradually decreased. The lowest grain size calculated at 9000 r / min was 9.8 nm. The resulting magnetic particles had small grain size and excellent dispersibility, providing a high-quality magnetic core for subsequent composite adsorbents.

[0019] Furthermore, the method of the present invention achieves uniform coating of SiO2 and effective grafting of APTES through high shear strengthening, and further improves the directional assembly of lignin on the inorganic shell through the high shear environment, avoiding active site shielding and structural collapse, and forming a structurally complete and interface-coordinated four-level core-shell system.

[0020] Furthermore, the method of the present invention employs a high-shear reactor, which has high mixing efficiency, fast mass transfer rate, and short reaction time, making it suitable for continuous / semi-continuous operation and easy to scale up for production.

[0021] Furthermore, the method of the present invention uses lignin extracted from agricultural waste cotton stalks as raw material, realizing the high-value utilization of biomass waste, which is in line with the green and sustainable development strategy.

[0022] The present invention also discloses a high-shear-strength lignin-based magnetic adsorbent prepared by the above method, which has excellent adsorption performance for Congo red. According to relevant experimental results, the sample prepared at 9000 rpm has a maximum adsorption capacity of 1329.6 mg / g for Congo red, which is 4.8 times higher than that of the sample prepared at 3000 rpm (228.7 mg / g). Attached Figure Description

[0023] Figure 1 This is a flowchart of the preparation method of the high-shear-strength lignin-based magnetic adsorbent of the present invention; Figure 2 The XRD patterns of the nano-Fe3O4 magnetic particles obtained in Examples 1-3 of this invention are shown below. Figure 3 The images are SEM images of nano-Fe3O4 magnetic particles obtained at different rotation speeds in Examples 1-3 of this invention. Where: a-3000 rpm; b-6000 rpm; c-9000 rpm; Figure 4 The image shows the FT-IR spectrum of the high-shear-strength lignin-based magnetic adsorbent prepared in Example 1 of this invention. Detailed Implementation

[0024] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0025] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0026] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0027] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”

[0028] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0029] This invention provides a method for preparing a high-shear-strength lignin-based magnetic adsorbent, such as... Figure 1 As shown, it includes the following steps: Step 1: Dissolve ferrous salts (Fe2+ and ferric salts) in water to prepare a mixed ferric salt solution; Step 2: Place the mixed iron salt solution obtained in Step 1 in a high-shear reactor. Under stirring conditions, add the precipitant to the mixed iron salt solution to carry out a high-shear co-precipitation reaction. After the reaction is completed, separate, wash and dry to obtain nano Fe3O4 magnetic particles. Step 3: Disperse the obtained nano Fe3O4 magnetic particles in anhydrous ethanol, add tetraethyl orthosilicate (TEOS), and react in a high-shear reactor. After the reaction is completed, separate, wash and dry in sequence to obtain Fe3O4@SiO2 core-shell particles. Step 4: Disperse the obtained Fe3O4@SiO2 core-shell particles in anhydrous ethanol, add alkaline lignin solution and 3-aminopropyltriethoxysilane (APTES), and react in a high-shear reactor. After the reaction is completed, separate, wash and dry to obtain Fe3O4@SiO2@APTES@lignin magnetic adsorbent (high-shear reinforced lignin-based magnetic adsorbent).

[0030] Preferably, in step 1, the divalent ferric salt is FeCl2·4H2O; the trivalent ferric salt is FeCl3·6H2O; and the Fe in the mixed ferric salt solution is Fe... 2+ with Fe 3+ The molar ratio is 1:1.5 to 1:2.5; the concentration of the mixed iron salt solution is 0.05 to 0.15 mol / L.

[0031] Preferably, in step 2, the precipitant is ammonia water, and the mass concentration of the ammonia water is 25%~28%; the volume ratio of the ammonia water to the mixed iron salt solution is 1:10~1:30; and the ammonia water is added at a rate of 1~4 mL / min.

[0032] Preferably, in step 2, the high-shear coprecipitation reaction is carried out at a rotation speed of 3000~9000 rpm, a reaction temperature of 70~90℃, and a reaction time of 10~40 min.

[0033] Preferably, in step 3, the mass ratio of the nano Fe3O4 magnetic particles to tetraethyl orthosilicate is 1:0.5 to 1:2; the volume ratio of the nano Fe3O4 magnetic particles to anhydrous ethanol is 1g:600mL. The addition of tetraethyl orthosilicate was carried out in a high-shear reactor at a rotation speed of 6000 rpm, a reaction temperature of room temperature, and a reaction time of 1 hour. Preferably, in step 4, the alkaline lignin solution is obtained by mixing alkaline lignin and ammonia. The mass ratio of the Fe3O4@SiO2 core-shell particles, basic lignin, and 3-aminopropyltriethoxysilane is 1:(1.5~2.5):(100~180); the amount of anhydrous ethanol used is 300mL. The reaction was carried out at 6000 rpm for 1 h at room temperature.

[0034] Preferably, in step 4, 15 mL of formaldehyde solution is added, and the formaldehyde solution is fed at a rate of 3 mL / min.

[0035] In the above technical solution, the rotor linear velocity of the high-shear reactor is 5~50 m / s.

[0036] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0037] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.

[0038] Example 1 A method for preparing a high-shear-strength lignin-based magnetic adsorbent includes the following steps: Step 1: Weigh 94 g FeCl2·4H2O and 2.7 g FeCl3·6H2O into a beaker, add 300 mL of deionized water, and stir continuously at 3000 rpm for 15 min in a high-shear reactor to fully dissolve and mix the raw materials to obtain a mixed iron salt solution. Subsequently, ammonia water (mass concentration 25%~28%) was slowly added dropwise to the mixed solution using a syringe pump, with the ammonia water feed rate controlled at 3 mL / min, and the feed was continued for 5 min (total amount 15 mL). After the ammonia water injection was completed, the reaction system was placed in a constant temperature environment of 70℃, and a high-shear co-precipitation reaction was continued at 3000 rpm for 40 min. After the reaction was completed, the product was repeatedly washed with a large amount of deionized water until the pH of the washing solution was neutral, and then vacuum dried at 60℃ for 12 h. Nano Fe3O4 magnetic particles were obtained by grinding and labeled as F3. Step 2: After thoroughly grinding the nano-Fe3O4 magnetic particles obtained in Step 1, weigh 2.0 g of the sample and add it to 300 mL of anhydrous ethanol. Disperse the sample by ultrasonication for 30 min. Slowly inject 1.0 mL of TEOS into the above mixed solution using a syringe pump, controlling the feed rate at 0.2 mL / min (the mass ratio of TEOS to Fe3O4 is approximately 1:1.87). After injection, react the sample in a high-shear reactor at 6000 rpm at room temperature for 1 h. After the reaction, wash the product until neutral and dry it under vacuum at 60 °C for 12 h to obtain Fe3O4@SiO2 core-shell particles, labeled as F3S6. Step 3: After grinding the Fe3O4@SiO2 core-shell particles obtained in Step 2, weigh 0.05 g of the sample and add it to 300 mL of anhydrous ethanol. Disperse the sample ultrasonically for 30 min. Dissolve 0.1 g of alkaline lignin in 20 mL of ammonia solution. After complete dissolution, add the dissolved lignin to the beaker. Add 7 mL of APTES to the mixture and slowly inject formaldehyde solution (as a crosslinking agent to promote covalent bonding between alkaline lignin and APTES) at a feed rate of 3 mL / min using a syringe pump. Continue injecting for 5 min (15 mL). Stir the mixture at 6000 rpm for 1 h at room temperature. After the reaction, wash the product until neutral and dry it under vacuum at 60℃ for 12 h to obtain Fe3O4@SiO2@APTES@lignin magnetic adsorbent (high shear-strengthened lignin-based magnetic adsorbent), labeled F3SA6.

[0039] Example 2 Unlike Example 1, the high-shear coprecipitation reaction in step 1 was carried out at a speed of 6000 rpm. The other steps were the same as in Example 1. The obtained nano Fe3O4 was labeled as F6, and the final adsorbent was labeled as F6SA6.

[0040] Example 3 Unlike Example 1, the high-shear coprecipitation reaction in step 1 was carried out at a speed of 9000 rpm. The other steps were the same as in Example 1. The obtained nano Fe3O4 was labeled as F9, and the final adsorbent was labeled as F9SA6.

[0041] Example 4 Unlike Example 1, the reaction temperature in step 1 is 80°C, while the other steps are the same as in Example 1.

[0042] Example 5 Unlike Example 1, the reaction temperature in step 1 is 90°C, while the other steps are the same as in Example 1.

[0043] Example 6 Unlike Example 1, the ammonia feed rate in step 1 is 1 mL / min (total 5 mL), while the other steps are the same as in Example 1.

[0044] Example 7 Unlike Example 1, the ammonia feed rate in step 1 is 2 mL / min (total 10 mL), while the other steps are the same as in Example 1.

[0045] Example 8 Unlike Example 1, the ammonia feed rate in step 1 is 4 mL / min (total 20 mL), while the other steps are the same as in Example 1.

[0046] Example 9 Unlike Example 1, the reaction time in step 1 is 10 min, while the other steps are the same as in Example 1.

[0047] Example 10 Unlike Example 1, the reaction time in step 1 is 20 min, while the other steps are the same as in Example 1.

[0048] Comparative Example 1 Unlike Example 1, in step 1, conventional mechanical stirring (500 rpm) was used instead of a high-shear reactor. The other steps were the same as in Example 1, and the resulting adsorbent was labeled C1.

[0049] Comparative Example 2 Unlike Example 2, in step 1, conventional mechanical stirring (500 rpm) was used instead of a high-shear reactor. The other steps were the same as in Example 2, and the resulting adsorbent was labeled C2.

[0050] Comparative Example 3 Unlike Example 3, in step 1, conventional mechanical stirring (500 rpm) was used instead of a high-shear reactor. The other steps were the same as in Example 3, and the resulting adsorbent was labeled C3.

[0051] Performance testing 1) The adsorbents prepared in Examples 1-3 and Comparative Examples 1-3 were tested for Congo red adsorption performance.

[0052] Adsorption experiment method: Weigh 0.1504 g of Congo red dye and add 300 mL of deionized water to form a dye solution with an initial concentration of 501.3 mg / L. Add 0.01 g of adsorbent to each solution, and stir continuously at 400 rpm for 5 h at a constant temperature of 25℃ until adsorption equilibrium is reached. After standing, take the supernatant and measure the absorbance at a wavelength of 496 nm using spectrophotometry. Calculate the equilibrium adsorption capacity using a standard curve. Each experiment was repeated three times, and the average value was taken.

[0053] The test results are shown in Table 1. As can be seen from Table 1, as the high-shear reactor rotation speed increased from 3000 rpm to 9000 rpm, the Fe3O4 particle size decreased from 13.2 nm to 9.8 nm, and the adsorption capacity significantly increased from 228.7 mg / g to 1329.6 mg / g, an increase of approximately 4.8 times. In contrast, the comparative examples C1, C2, and C3, prepared using conventional mechanical stirring, had Fe3O4 particle sizes of approximately 25 nm, with adsorption capacities of 118.3 mg / g, 112.5 mg / g, and 106.8 mg / g, respectively, far lower than the samples prepared by high-shear enhancement. This indicates that high-shear enhancement can effectively refine Fe3O4 particles, improve dispersibility, and significantly enhance the adsorption performance of the adsorbent.

[0054] Table 1. Comparison of adsorbent performance under different rotation speeds

[0055] 2) XRD analysis X-ray diffraction analysis was performed on the Fe3O4 samples prepared in Examples 1-3, and the results are as follows: Figure 2As shown, samples prepared at different rotation speeds all exhibited typical spinel structure diffraction peaks (JCPDS No. 19-0629), without α-Fe2O3 or γ-Fe2O3 impurity phase peaks. The grain sizes calculated by the Scherrer formula were 13.2 nm (3000 rpm), 11.7 nm (6000 rpm), and 9.8 nm (9000 rpm), respectively, showing a monotonically decreasing trend with increasing rotation speed.

[0056] 3) The Fe3O4 samples prepared in Examples 1-3 were observed using a scanning electron microscope, such as... Figure 3 As shown, the sample prepared at 3000 rpm contained a small number of irregular aggregates with a size greater than 20 nm; at 6000 rpm, the particles were nearly spherical and uniform in size, with an average particle size of about 12 nm; at 9000 rpm, the particle size was further reduced to about 10 nm, and the dispersibility was optimal.

[0057] 4) FT-IR analysis Fourier transform infrared spectroscopy analysis was performed on the Fe3O4@SiO2@APTES@lignin magnetic adsorbent prepared in Example 1, as follows: Figure 4 As shown. At 580 cm -1 The presence of Fe-O bond stretching vibration peaks at 1080–1100 cm⁻¹ confirms the existence of Fe₃O₄ magnetic nuclei; [further details about the peaks are needed to complete the translation.] -1 The appearance of Si-O-Si asymmetric stretching vibration peaks at 1560–1600 cm⁻¹ confirms the formation of the SiO₂ coating layer; the presence of peaks at 1560–1600 cm⁻¹ further confirms the formation of the SiO₂ coating layer. -1 At 3400 cm⁻¹, a superposition peak appears between the -NH₂ bending vibration in APTES and the C=C stretching vibration of the lignin aromatic ring skeleton; at 3400 cm⁻¹... -1 Broad peaks of OH stretching vibrations of phenolic and alcoholic hydroxyl groups in lignin were observed nearby. These results confirm the successful construction of the Fe3O4@SiO2@APTES@lignin quaternary structure. The SiO2 stable shell coats the outer surface of the Fe3O4 magnetic core, the APTES coupling layer is covalently grafted onto the outer surface of the SiO2 stable shell, and the lignin adsorption layer is chemically bonded to the APTES coupling layer.

[0058] 5) Adsorption kinetics analysis The adsorption kinetics of Example 3 (F9SA6) were studied. The experimental data were fitted using a pseudo-first-order kinetic model, a pseudo-second-order kinetic model, and an intraparticle diffusion model, respectively. The results are shown in Table 2. It can be seen that the pseudo-second-order kinetic model... R²The value was 0.9971, which is much higher than the 0.8847 of the pseudo-first-order kinetic model and the 0.7938 of the intraparticle diffusion model. This indicates that the adsorption process is dominated by chemisorption, and the adsorption rate is controlled by chemical interactions such as electrostatic interactions, hydrogen bonds, and π-π stacking between the active sites on the adsorbent surface and Congo red molecules.

[0059] Table 2. Fitting parameters of the kinetic model for F9SA6 adsorption of Congo red.

[0060] 6) Adsorption isotherm analysis The adsorption equilibrium data of Example 3 (F9SA6) were fitted using the Langmuir and Freundlich models, and the results are shown in Table 3. Table 3 shows that the Freundlich model... R² (0.9928) higher than the Langmuir model. R 2 (0.9829), and 1 / n The value is 0.9426 (between 0 and 1), indicating that the adsorption process conforms to the multilayer adsorption mechanism of heterogeneous surfaces, and that adsorption is favorable and spontaneous. The synergistic effect of electrostatic attraction, hydrogen bonding, and π-π stacking significantly improves the accessibility and binding strength of active sites.

[0061] Table 3. Fitting parameters of the isotherm model for F9SA6 adsorption of Congo red.

[0062] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.

Claims

1. A method for preparing a high-shear-strength lignin-based magnetic adsorbent, characterized in that, Includes the following steps: S1: Dissolve ferrous salts and ferric salts in water to obtain a mixed ferric salt solution; S2: The mixed iron salt solution was placed in a toothed high-shear reactor. Under stirring conditions, the precipitant was added to the mixed iron salt solution to carry out a high-shear co-precipitation reaction. After the reaction was completed, the solution was separated, washed, and dried to obtain nano Fe3O4 magnetic particles. S3: The obtained nano-Fe3O4 magnetic particles were dispersed in anhydrous ethanol, and tetraethyl orthosilicate was added. The reaction was carried out in a high-shear reactor. After the reaction was completed, the particles were separated, washed and dried in sequence to obtain Fe3O4@SiO2 core-shell particles. S4: Fe3O4@SiO2 core-shell particles were dispersed in anhydrous ethanol, and alkaline lignin solution and 3-aminopropyltriethoxysilane were added. The reaction was carried out in a high-shear reactor. After the reaction was completed, the particles were separated, washed and dried in sequence to obtain a high-shear reinforced lignin-based magnetic adsorbent.

2. The method for preparing a high-shear-strength lignin-based magnetic adsorbent according to claim 1, characterized in that, In S1, the divalent ferric salt is FeCl2·4H2O; the trivalent ferric salt is FeCl3·6H2O; and the Fe in the mixed ferric salt solution... 2+ with Fe 3+ The molar ratio is 1:1.5 to 1:2.5; The concentration of the mixed iron salt solution is 0.05~0.15 mol / L.

3. The method for preparing a high-shear-strength lignin-based magnetic adsorbent according to claim 1, characterized in that, In S2, the precipitant is ammonia water, and the mass concentration of the ammonia water is 25%~28%; the volume ratio of the ammonia water to the mixed iron salt solution is 1:10~1:30; and the ammonia water is added at a rate of 1~4 mL / min.

4. The method for preparing a high-shear-strength lignin-based magnetic adsorbent according to claim 1, characterized in that, In S2, during the high-shear coprecipitation reaction, the high-shear reactor rotates at 3000~9000 rpm, the reaction temperature is 70~90℃, and the reaction time is 10~40 min.

5. The method for preparing a high-shear-strength lignin-based magnetic adsorbent according to claim 1, characterized in that, In S3, the mass ratio of the nano Fe3O4 magnetic particles to tetraethyl orthosilicate is 1:0.5 to 1:2; the ratio of the nano Fe3O4 magnetic particles to anhydrous ethanol is 1g:600mL. The addition of tetraethyl orthosilicate is carried out in a high-shear reactor at a rotation speed of 3000~9000 rpm, a reaction temperature of room temperature, and a reaction time of 0.5~2 hours.

6. The method for preparing a high-shear-strength lignin-based magnetic adsorbent according to claim 1, characterized in that, In S4, the alkaline lignin solution is obtained by mixing alkaline lignin and ammonia. The mass ratio of Fe3O4@SiO2 core-shell particles, alkaline lignin, and 3-aminopropyltriethoxysilane is 1:(1.5~2.5):(100~180); the molar ratio of Fe3O4@SiO2 core-shell particles to anhydrous ethanol is 0.03~0.08 g:200~400 mL. The reaction was carried out at a rotation speed of 3000~9000 rpm for a reaction time of 0.5~2 h at room temperature.

7. The method for preparing a high-shear-strength lignin-based magnetic adsorbent according to claim 1, characterized in that, In step S4, after adding alkaline lignin solution and 3-aminopropyltriethoxysilane, formaldehyde solution is added. The feed rate of formaldehyde solution is 1~5 mL / min; the amount of formaldehyde solution used is 10~20 mL.

8. The method for preparing a high-shear-strength lignin-based magnetic adsorbent according to claim 1, characterized in that, The rotor linear velocity of the high-shear reactor is 5~50 m / s.

9. A high-shear-strength lignin-based magnetic adsorbent, characterized in that, The adsorbent is prepared by any one of the preparation methods described in claims 1 to 8; the microstructure of the adsorbent has a four-level core-shell structure, including a Fe3O4 magnetic core layer, a SiO2 stable shell layer, an APTES coupling layer, and a lignin adsorption layer; the SiO2 stable shell layer is coated on the outer surface of the Fe3O4 magnetic core, the APTES coupling layer is covalently grafted onto the outer surface of the SiO2 stable shell layer, and the lignin adsorption layer is chemically bonded to the APTES coupling layer.

10. The application of the high shear-strengthened lignin-based magnetic adsorbent of claim 9 in the adsorption of Congo red.